COMPARISON OF 30 ML AND 60 ML FOLEY CATHETER FOR CERVICAL RIPENING - Wijepala, Jagath; Najimudeen, M (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿Object: This study is to compare the efficacy of 60ml with 30ml of intracervical balloon (Foley) catheter for pre induction cervical ripening. Material and methods: This is a study of 88 multigravida mothers with the confirmed period of gestation of 40 weeks and 2 days. The period of study was from 1.11.2008 to 1.5.2010 at the Colombo south teaching hospital and Castle street hospital for women in Colombo Sri Lanka A total of 88 mothers participated in the study. The mother were equally distributed to the two groups. (44 mothers in 60 ml group and 44 mothers in 30 ml group) Results: Higher proportion of cervical favorability was achieved in 60 ml Foley catheter group compared to 30ml group. This difference was statistically significant (p<0.001). There was no significant difference between the 30ml volume and 60ml volume group in relation to maternal age. (p=0.23) Higher proportion of Vaginal delivery was achieved in 60ml Foley balloon group compared to 30ml Foley balloon group. This proportion was statistically significant. (p=.0.01) Cervical ripening using Foley balloon inflated with 60ml was more likely to achieve delivery within 30 hours compared with 30ml group (p<0.001).Duration of labour was significantly short in 60ml group(p=0.001).